The Effective College Teacher: Views of Students - Ronato S. Ballado (Scientia Publica Media, 2025)
The teacher is one of, if not the most essential, factors in the teaching-learning process. The study explored the qualities of effective college teachers through the lens of the most important stakeholder of education - the students. The study involved college students of the University of Eastern Philippines Main Campus as respondents sampled proportionally from different year levels and colleges. The study utilized a descriptive research design and an open-ended questionnaire as an instrument. Responses of the students were classified into themes, utilizing frequency counts, percentages, and ranking as statistical tools. Characteristics of teachers were generally grouped into two categories – affective competence and professional competence. For students, an effective teacher is kind, understanding, approachable, and has good interpersonal relations for affective competence and knowledgeable, innovative, punctual, has good communication skills, and has technical know-how for professional competence. The two groups of competence are overlapping, as one cannot be easily demonstrated without the other. The students have varied conceptions of what an effective college teacher is. Learning institutions may consider these competencies in the evaluation of collegiate faculty members. Considering the effective characteristics of teachers in the evaluation of faculty members will redound to the overall improvement of the competence of faculty members.